Clusters of Stressful Events and Mental Health in Aging Women - Dóris Firmino Rabelo; Simone Seixas da Cruz (Paidéia (Ribeirão Preto))
Abstract: Specific stressful events in aging women impact their mental health. This study found the profiles of middle-aged and older women regarding the number of stressful events and their mental health and characterized the sociodemographic and health differences between the groups. In total, 545 middle-aged and older women answered an online form containing the Self-Reporting Questionnaire and the Stressful Events in Old Age inventory. Neighborhood based clustering and bivariate analyses were performed. Results showed (1) a cluster with a higher number of stressful events and worse mental health that consisted of middle-aged women under greater social vulnerability and (2) a cluster with a lower number of stressful events and better mental health that consisted of older white women with good economic and psychosocial conditions. These profiles show the scenarios most susceptible to stressors and mental health problems.